DONATION FOR CHURCH CONSTRUCTION VIEWED FROM SAYYID THANTHAWI'S PERSPECTIVES - Muchlis Bahar (Universitas Islam Negeri Ar-Raniry, 2023)
This research aimed at investigatingÂ Sayyid Thanthawi's ijtihad pattern and methodology for deciding the law on making donations for church construction. As stated by Islamic teachings, Christians do not regard God to be One since they believe in the Trinity (the Father, the Son, and the Holy Spirit). Within the national state, however, Muslims and Christians coexist, work together, and assist one another. Conflicts of interest in coexistence might emerge as a result of religious differences. This current study is library research usingÂ qualitative descriptive analysis. The data used were secondary data in the form of books written by Sheikh Sayyid Thanthawi, Mufti of the Arab Republic of Egypt, as well as other relevant books. This research found that from Sayyid Thanthawi's viewpoint, a Muslim is permitted to donate to the construction of a church. Sayyid Thanthawi's Ijtihad is moderate since it considers the greater benefit and fosters harmony among religious communities, without ignoring the demands of the Qur'anic text. The ijtihad approach employed is the maslahah theory, which takes into account the benefits and harm that would be caused by the Fatwa's issuing. The implication of this ijtihad is the establishment of concord and peace between Muslims and Christians in Egypt. However, some Egyptian religious scholars restrict donations to church construction, arguing that it is the same as donating to the development of gambling businesses and nightclubs.